Mapping the landscape of a wide interdisciplinary curriculum: a network analysis of a Korean university and the lessons learnt. (14th February 2022) - Ryu, Hokyoung; Kim, Jieun
Abstract: Interdisciplinary programmes have become common in universities and research groups' curricula. This study conducted a network analysis on a Korean university's undergraduate curriculum and used several visualisation tools to assess keywords across courses and departments, revealing epistemological distances between the courses/departments and their concepts of study. This data-driven methodology defined the characteristics of close or neighbouring departments, making it possible to implement narrow interdisciplinarity through common subjects within the courses. Interestingly, a further projected network could determine the implicit relations between departments that are not considered close, which would make it possible to implement a wide interdisciplinary curriculum. The data-driven network analysis conducted in this study contributes to searching for new programmes for specific levels of interdisciplinarity on an empirical basis.